Pharmacological and Phytochemical investigation of plant Zingiber Zerumbet having anti-ulcer activity - Kumar, Aditya; Basedia, Deepak Kumar; Dubey, Balkrishna; Shah, Sunil Kumar; Goutam, Sandra (Journal of Biomedical and Pharmaceutical Research, 2024)
This study investigates the anti-ulcerogenic properties of Zingiber zerumbet using a rat model subjected to ulcerogenic agents. The hydroalcoholic extract of Zingiber zerumbet was evaluated for its efficacy in mitigating ulcer formation, measured through the number of ulcers, ulcer index, and gastric pH levels. Results demonstrated that the extract significantly reduced both the number of ulcers (from 9.80 ± 0.75 in the control group to 0.25 in the treated groups) and the ulcer index (from 6.25 ± 0.30 in the control to 0.52 ± 0.15 in the extract-treated group). Additionally, the gastric pH improved markedly, with treated groups showing pH levels of 6.85 ± 0.75 and 6.75 ± 0.35, compared to 3.45 ± 0.32 in the control group. The qualitative phytochemical analysis revealed the presence of flavonoids, saponins, and alkaloids, which are known for their therapeutic effects. These findings underscore the potential of Zingiber zerumbet as a natural remedy for gastric ulcers, providing a basis for further research into its active constituents and mechanisms of action Keywords: Zingiber zerumbet, anti-ulcerogenic, gastric ulcers, rat model, ulcer index, gastric pH, phytotherapy, herbal medicine, flavonoids